Closed-loop ring resonator topology for bandpass filter applications - Norfishah Ab Wahab; M. N. Md Tan; M. N. Hushim (Institute of Advanced Engineering and Science, 2020)
This paper presents a single mode pseudo-elliptic bandpass resonator based on closed-loop ring topology. The resonator is built from six quarter wavelength transmission lines to form a square closed-loop ring structure. This structure creates transmission zeros at the lower and upper sidebands so that high selectivity bandpass filter response is achieved. The advantage of this topology is that the design is less complex since no perturbation is needed on the ring lines for creation of transmission zeros. Higher-order filters can be constructed by introducing quarter-wavelength coupled-lines, coupled at both input and output of the closed-loop ring resonator. For proof of concept, the filters are designed at 10 GHz up to 3rd order, simulated using full-wave electromagnetic simulator on microstrip substrate, FR-4 with characteristics given as Ԑr = 4.70, h = 1.499 mm and tan δ = 0.012. The filters are simulated and responses are found to be agreeable with the proposed idea.